DIAGNOSIS LABORATORIK ANEMIA DEFISIENSI BESI - Margina, Dina Sophia; Herawati, Sianny; Sutirta Yasa, I W P (E-Jurnal Medika Udayana; vol 3 no 1 (2014):e-jurnal medika udayana)
Iron deficiency anemia is a decreament of iron level in the body. Iron deficiency anemia is oftenly seen, especially in the tropical countries or the third world country that associated with social economic rate. Iron deficiency anemia happens in more than one third world’s population. Iron deficiency anemia can be caused by chronic hemorrhage, low intake of iron, absorption disturbance, and increasement of demand. To diagnose iron deficiency anemia, laboratoric examination is needed. The treatment can be causal treatment, iron supplementation and another additional treatment.
Keywords: iron deficiency anemia